Islamisme dan Habib Preneur: Dinamika Bisnis Para Habib di Kalimantan - Basrian, Basrian; Nor'ainah, Nor'ainah; Maimanah, Maimanah (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
There is something interesting about the business of these habibs, namely their